From Care to Citizenship: Rethinking Early Childhood Education Through the Lens of Sustainability and Participation - Zoi Apostolou (Journal of Education for Sustainable Development Studies, 2026)
Education for active citizenship constitutes a central pillar of contemporary educational policies at both international and national levels. In Greece, recent legislative initiatives and the new curriculum “Actions of an Active Citizen” (Government Gazette 6048/B'/1-11-2024) introduce 17 thematic areas aligned with the Sustainable Development Goals (SDGs), implemented from preschool to upper secondary education. The main objective is to establish active citizenship as a concept and pedagogical practice, promoting democracy, cooperation, and social responsibility. This study focuses on early childhood education and explores how preschool teachers in the Cyclades (North Aegean, Greece) design and implement active citizenship projects within this curriculum framework, as well as how they evaluate their effectiveness. The research aims to capture pedagogical practices that foster democratic learning and sustainable development through participation, collaboration, and the engagement of both the school and the local community. Specifically, it examines how they conceptualize the notion and pedagogical role of active citizenship in early childhood education, what forms of pedagogical practices and activities they implement, and what challenges or needs they identify for the effective integration of active citizenship into their educational practice. The study was conducted during the 2024–2025 school year and targeted all preschools across the Cyclades islands. Data were collected through a structured questionnaire and were analyzed using SPSS v.29. The results indicated that preschools can serve as living laboratories of democracy and social transformation. Through intentional, reflective pedagogy, active citizenship becomes a way of life within the educational experience. Early childhood emerges as a fertile ground for nurturing values such as empathy, solidarity, and responsibility. The case of the Cyclades illustrates how small school communities can function as micro-democracies, where children learn to listen, collaborate, and care for their shared world.